Breastfeeding Experience of Adolescent Mothers in Bengkulu City - Tanjung, Yeni Efrilia Indrianti; Simanjuntak, Betty Yosephin; Marleni, Wisuda Andeka (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Backgrounds: The number of early marriages has continued to increase since the COVID-19 pandemic, the unpreparedness of parenting for adolescent mothers will have an impact on the nutritional status of children, especially in breastfeeding. Objective: The purpose of this study was to obtain in-depth information related to breastfeeding experiences in adolescent mothers. Methods: This study used qualitative methods on 6 adolescents aged under 20 years who have babies aged 0-24 months, conducted in-depth interviews about breastfeeding experiences including intentions to act, thoughts and feelings, social support, breastfeeding references, enabling breastfeeding outside the home and socio-cultural context. Results: The findings of this study showed that adolescent mothers failed to provide exclusive breastfeeding due to supplementary feeding to infants before the age of 6 months. However, adolescent mothers continue to breastfeed their babies because of the perceived benefits of breastfeeding, social support in the form of motivation and counseling from families and health workers. Adolescent mothers experience physical experiences of soreness, abrasions, swelling and pain in the breasts. They are pleased because they believe that it can make the inner bond between mother and baby closer and more intimate. There are taboos and recommendations in society that are believed to affect breastfeeding babies such as abstinence from consuming long-term foods or recommendations to consume vegetables that are believed to facilitate breast milk. Conclusions: Painful breastfeeding does not stop adolescent mothers from breastfeeding. Adolescent mothers continue to breastfeed although not exclusively.